Biotecnologia: Perfil dos grupos de pesquisa no Brasil - Marco Aurélio Alves(de Mendonça; Rogério Edivaldo Freitas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The study aims to map the human capital profile involved with the biotechnology in Brazil. We used descriptive statistical analysis. The database was set up exclusively for this study starting from information of the innovation website of the Brazilian Ministry of the Science and Technology. The investigation demonstrated the increment of number of research groups in the last years. This fact results of the efforts undertaken by a series of agents, especially the federal government. Besides, the data indicate that the researchers mainly concentrate on the South and Southeast regions of the country, with significant participation of agrarian, biological and health sciences.
Keywords: I21; J24; O15; 330